Synthesis and characterization of micro-and mesoporous materials for catalytic biomass upgrading - Jorge, Erlen Yizenia Cruz (Universidade Federal de São Carlos, 2019)
In the last years, biomass, especially lignocellulosic, has emerged as an alternative source of carbon. From the fractionation of lignocellulosic biomass, a series of chemical compounds or platforms can be obtained, having multiple industrial applications: lubricants, solvents, additives for fuels and personal hygiene products. Industrially, the fractionation process uses mineral acids, high temperatures and pressure, which has led to the emergence of solid catalysts such as micro and mesoporous materials. These are separated from the reaction medium more easily and are usually less industrially aggressive. On the other hand, to carry out the fractionation of the lignocellulosic biomass, catalysts with both Brönsted and Lewis sites are needed. So far, to carry out the different steps of this fractionation are used mixtures of catalysts, one that works as Brönsted acid and other as Lewis acid. The objective of this work is to synthesize bifunctional catalysts that are able to perform cascade reactions for the recovery of compounds derived from lignocellulosic biomass. To achieve this, two catalysts were synthesized, characterized and evaluated: zeolite-β magnetically recoverable in its acid form and exchanged with transition metal ions such as iridium, iron and palladium; as well as dendritic silica functionalized with sulfonic acid. Despite the enormous industrial importance of zeolites, their applications in technological processes in which high added value products are obtained and involving large molecules are limited due to the small size of their pores. The need of materials with a pore size greater than a nanometer boosted research in the field of materials science through the synthesis of mesoporous materials. In the present work, we proceeded to the synthesis of two materials: one microporous, very useful for the valorization of small molecules and another mesoporous, for the fractionation of more complex molecules such as sugars and disaccharides.
Síntese e caracterização de materiais micro e mesópolos para promoção de biomassa catalítica
Keywords: Lignocellulosic biomass; β-zeolite; Dendritic silica; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA